Microbial Paraffin-Removal Technology Using Paraffin-Degrading and Biosurfactant-Producing Strain - Liu, Jianghong; Chen, Yitong; Xu2, Ruidan; Jia3, Yunpeng; Wang, Jian; Lu, Yan; Sun, Hong; Yuan, Dandan (Asian Journal of Chemistry, 2014)
The paraffin-degrading strain, isolated from waxy oil production wells in Daqing oilfield, were obtained by separation and purification experiment. The paraffin-degrading strain P1 was identified through 16S rDNA sequence analysis, which exhibited the highest similarities to Bacillus anthracis strain XFB-BN. The biosurfactant-producing strain was obtained by laboratory saved. After paraffin-degrading and biosurfactant-producing strain treatment, the paraffin degradation rate could reach to 68.2 %, the paraffin prevention rate could reach to 80.7 %, the reduction rate of crude oil viscosity was 62.4 %. By analyzing the data, the paraffin-degrading and biosurfactant-producing strain had better effect on microbial prevention of wax deposition.